ANALISIS RISIKO SIKAP KERJA DENGAN KELUHAN MUSCULOSKELETAL DISORDER PADA PORTER STASIUN SURABAYA GUBENG - Ervin Putri Puspitasari (Universitas Airlangga, 2019)
Musculoskeletal disorders (MSDs) is a type of disorder in the body structure caused or compounded by a unergonomic work attitude. One of jobs at Surabaya Gubeng Station which possible to increase the risk of Musculoskeletal disorders is porter. This study aimed to analyze risk of work attitude with complaint of Musculoskeletal Disorders at Surabaya Gubeng Station’s porter. This study was analytic observational research with cross sectional research design. Data obtained from 60 porters who worked at Surabaya Gubeng Station. Musculoskeletal disorders were obtained from Nordic Body Map (NBM) observation sheet. Characteristics of respondents obtained from interview. Work attitude risk was obtained by Rapid Entire Body Assessment (REBA) method. In this study the independent variable was the risk of work attitude. Dependent variable was a complaint of Musculoskeletal disorders. Data were tested using Cramer Coefficient. The prevalence of MSDs found in this study was 86.7% with low category was counted 96.2% and medium category was 3.8%. Musculoskeletal disorders in the porter occur at night before bed and frequency of Musculoskeletal disorders occurs every 1-2 times/ week. Porter experienced most MSDs complaints on the body at the right shoulder, left shoulder, right calf, and left calf. Cramer coefficient showed a value of 0.197 on risk of right body work attitude and Cramer Coefficient of 0.046 on risk of left body work attitude. The conclusion of this research was the risk of right and left body work attitude was not affect complaint of Musculoskeletal Disorder. Keywords: musculoskeletal disorder, porter, station, risk of work attitude